Management of Phenylketonuria: Current and Future Perspectives - Tejas J. Shah1 , Dipika Baria2 , Shruti Brahmbhatt3 , DVSS Ramavataram4 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Phenylketonuria (PKU) is an inborn error of phenylalanine (phe) and tyrosine (tyr) metabolism. It is anautosomal recessive disease occurred due to deficiency of liver enzyme phenylalanine hydroxylase (PAH).Hence, phe is not converted to tyr and phe is accumulated in the body. Phe thus channeled to alternativeroutes of metabolism and forms Phenylketones excreted in urine. Early treatment is essential to preventmental retardation and other intellectual disabilities. Dietary treatment remains the main cornerstone tomanage PKU since last 3-4 decades. A diet low in Phe supplemented with special amino acids formulasmust be started soon after diagnosis within seven days of life. Inspite of good results obtained from dietarytreatment in PKU, still there are some issues with palatability of the dietary formulations. There are alsoissues of nutritional deficiencies of vitamins like calcitriol and cobalamin (B12). Poor cognitive and executivefunctions have been observed in patients who do not follow proper dietary treatment. Attempts have alsobeen made to increase the palatability of food under dietary management. Role of large neutral amino acids(LNAAs) and glycomacropeptides (GMP; found in bovine milk) as a newer dietary management have alsobeen explored. In recent era, advances occurred in terms of genetic therapy and enzyme replacement therapywhich opened a new door towards management of PKU. In this review, various treatment aspects of PKUare discussed and explored.